2018
DOI: 10.1155/2018/3417648
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Evaluation of Soleal Vein Diameter by Ultrasound Is Beneficial for Prophylaxis of Deep Vein Thrombosis after Total Knee or Hip Arthroplasty

Abstract: Purpose The purpose of this retrospective study was to determine the association between preoperative soleal vein (SV) diameter and deep vein thrombosis (DVT) following total joint arthroplasty (TJA). Methods A total of 402 patients were enrolled, with 229 patients undergoing total knee arthroplasty (TKA) and 173 patients undergoing total hip arthroplasty (THA). Ultrasonography was performed 1-3 days preoperatively, on postoperative days 1, 3, and 7, or before discharge and during follow-up. The SV diameter wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…And the veins are therefore subjected to a more uniform pressure similar to intermuscular pressure. Some studies found that the intermuscular vein is the location where DVT often occurs, and soleus vein dilatation is an independent risk factor for deep venous thrombosis after orthopedic surgery [31,32]. Thus, the results obtained in this study could be considered as one of the possible mechanisms to explain that ankle pump exercise can prevent intramuscular venous thrombosis, which also needs to be further studied.…”
Section: Discussionmentioning
confidence: 60%
“…And the veins are therefore subjected to a more uniform pressure similar to intermuscular pressure. Some studies found that the intermuscular vein is the location where DVT often occurs, and soleus vein dilatation is an independent risk factor for deep venous thrombosis after orthopedic surgery [31,32]. Thus, the results obtained in this study could be considered as one of the possible mechanisms to explain that ankle pump exercise can prevent intramuscular venous thrombosis, which also needs to be further studied.…”
Section: Discussionmentioning
confidence: 60%
“…However, patients undergoing TKA were at high risk for VTE [7]. End-stage OA patients characterized with pain and high age could increase the risk for DVT [22,23]. To survey the incidence of surgery-related DVT, the incidence of patients showing DVT before surgery must be subtracted from the total of the incidences before and after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…ICDVTs were found in 33% (65/195) of 215 patients undergoing angiography, and calf muscular veins were the most common site. Yao et al 17 . studied the relationship between soleus vein thrombosis and joint replacement surgery and found that 78 (19.4%) of 402 patients had DVTs after total knee or hip replacement.…”
Section: Methodsmentioning
confidence: 99%
“…Yao et al . 17 studied the relationship between soleus vein thrombosis and joint replacement surgery and found that 78 (19.4%) of 402 patients had DVTs after total knee or hip replacement.…”
Section: Methodsmentioning
confidence: 99%